Frances Newman : Southern Satirist and Literary Rebel - Wade, Barbara Ann, 1947- (Book collections on Project MUSE., 1998)
Although Frances Newman's experimental novels (The Hard-Boiled Virgin, 1926, and Dead Lovers are Faithful Lovers, 1928) have recently begun to receive serious critical attention, this is the first published book-length study to focus both on Newman's life and on her fiction. Barbara Ann Wade draws from the novelist's personal correspondence and newspaper articles to reveal a vibrant, independent woman who simultaneously defied and was influenced by the traditional southern society she so aptly satirized in her writing.